2010
DOI: 10.1063/1.3462979
|View full text |Cite
|
Sign up to set email alerts
|

Force-controlled spatial manipulation of viable mammalian cells and micro-organisms by means of FluidFM technology

Abstract: The FluidFM technology uses microchanneled atomic force microscope cantilevers that are fixed to a drilled atomic force microscope cantilevers probeholder. A continuous fluidic circuit is thereby achieved extending from an external liquid reservoir, through the probeholder and the hollow cantilever to the tip aperture. In this way, both overpressure and an underpressure can be applied to the liquid reservoir and hence to the built-in fluidic circuit. We describe in this letter how standard atomic force microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
81
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 34 publications
1
81
0
Order By: Relevance
“…1a). It was previously shown that chosen microorganisms adsorbed on a glass surface in liquid can be attached to the cantilever aperture by application of underpressure, moved, and released onto another defined position on the same surface by application of a short overpressure pulse (36). Here we demonstrate that this protocol can be extended to isolate bacteria from environmental samples.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…1a). It was previously shown that chosen microorganisms adsorbed on a glass surface in liquid can be attached to the cantilever aperture by application of underpressure, moved, and released onto another defined position on the same surface by application of a short overpressure pulse (36). Here we demonstrate that this protocol can be extended to isolate bacteria from environmental samples.…”
mentioning
confidence: 81%
“…To explore and establish FluidFM for single-bacterium isolation, different parameters were tested and optimized to ensure efficient isolation of a wide range of randomly chosen bacteria from environmental samples. Cantilevers with an aperture diameter of 8 m were used; however, instead of cantilevers with a default channel height of 1 m, as used in previous studies (36,37,51), cantilevers with a channel height of only 0.5 m were used, because they ensured that the targeted bacteria remained confined at the aperture, where they could be easily spotted, and were not sucked into the channel of the probe. Plasma cleaning and coating the cantilever with PLL-g-PEG reduced the chance that a bacterium would irreversibly bind to the cantilever (38).…”
Section: Resultsmentioning
confidence: 99%
“…These modified pyramids can be applied as functional tips in Atomic Force Microscopy (AFM) based liquid deposition techniques, such as dip‐pen nanolithography (DPN),5 Nano‐Scale Dispensing (NADIS),6–8 and fountain pen based lithography 9, 10. An emerging application of fluidic AFM is in single cell biological or biophysical experiments 11. Pyramids containing nano‐apertures could find application as advanced electrospray emitters for the generation of nano‐scale droplets 12.…”
Section: Introductionmentioning
confidence: 99%
“…3 Previously, single-cell force spectroscopy has been successfully performed by various groups using AFM cantilevers functionalized with cell-adhesive ligands. 2931 Such cantilevers have been used to pick up individual cells and bring them in contact with a desired surface.…”
mentioning
confidence: 99%